2019
DOI: 10.1109/access.2019.2951587
|View full text |Cite
|
Sign up to set email alerts
|

Data Collection Through Mobile Vehicles in Edge Network of Smart City

Abstract: With increasing technological facilities, billions of sensor devices are deployed in the smart city, which allows to sense and collect the status and information of all kinds of infrastructures in the city. Those large number of sensing nodes form many self-organized wireless sensor networks (WSNs). Although the single WSN has been widely studied by researchers. However, few studies have focused on how to effectively connect to Internet of Things (IoT) and collect data in many decentralized WSNs of smart city … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 41 publications
0
24
0
Order By: Relevance
“…Luo et al [38] proposed a data collection scheme in smart city using vehicles, the sensing devices were widely deployed to detect the status of basic infrastructures, the vehicles sent sensing data from sensing devices to data center, then the data center could make scientific decisions. The authors of [39] proposed to collect data through unmanned aerial vehicle in a trust way, the energy consumption of system was decreased by optimizing the unmanned aerial vehicle's trajectory.…”
Section: Background and Related Workmentioning
confidence: 99%
“…Luo et al [38] proposed a data collection scheme in smart city using vehicles, the sensing devices were widely deployed to detect the status of basic infrastructures, the vehicles sent sensing data from sensing devices to data center, then the data center could make scientific decisions. The authors of [39] proposed to collect data through unmanned aerial vehicle in a trust way, the energy consumption of system was decreased by optimizing the unmanned aerial vehicle's trajectory.…”
Section: Background and Related Workmentioning
confidence: 99%
“…With the development of Internet of Things (IoT), there will be more than 20 billion IoT devices by 2020 [1][2][3]. Most of these IoT devices are deployed at the edge of the network [4][5][6]. Due to the huge number of these IoT devices and the development of micro-processing technology, their computing and storage capabilities have greatly improved.…”
Section: Introductionmentioning
confidence: 99%
“…However, the Edge network is an open network with various IoT devices in various forms connected [19][20][21]. For example, Luo et al [4] gave a typical application of smart city as shown in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations